ANALISIS EFEKTIVITAS MESIN SCREW PRESS MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS PABRIK KELAPA SAWIT SOLOK SELATAN - Syukra, Afif Ahmad; Putri, Gustiarini Rika (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2024)
One of the industries in South Solok is a manufacturing company engaged in the Palm Oil Processing (PKS) industry. In order to maintain the quality and excellence of its products, this company must carry out more maintenance and monitoring of the smoothness of its production process. One of the more maintenance that must be carried out in this industry is maintenance of the screw press machine which often experiences obstacles during production, if a problem occurs with this machine, the processing process at the next station will be disrupted and can even stop operating. After conducting interviews with field supervisors, it can be concluded that screw press machines often experience problems such as stopping while operating due to less than optimal maintenance, and the age of the machine is old.